1979
DOI: 10.1021/jm00191a012
|View full text |Cite
|
Sign up to set email alerts
|

Improved antitumor effects in 3'-branched homologs of 2'-deoxythioguanine. Synthesis and evaluation of thioguanine nucleosides of 2,3-dideoxy-3-(hydroxymethyl)-D-erythro-pentofuranose

Abstract: The 3-(hydroxymethyl) branched homologue of 2-deoxyribofuranose was synthesized from the corresponding branched ribofuranose 2-O-(S-methyl dithiocarbonate) with tributyltin hydride in the first direct, one-step deoxygenation at C-2 of a ribofuranose. Nucleoside coupling afforded the corresponding 3'-branched 2'-deoxyribonucleosides of thioguanine. The alpha- and beta-nucleosides were equally inhibitory to growth of WI-L2 human lymphoblastoid cells, were phosphorylated and incorporated into the DNA of Mecca lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(33 citation statements)
references
References 10 publications
(33 reference statements)
0
31
0
2
Order By: Relevance
“…To produce carbon-sulfur-linked glycoconjugates by the proposed thio-click approach, 3,4,5,7-tetra-Obenzoyl-2,6-anhydro-1-deoxy-d-gluco-hept-1-enitol I (Tóth & Somsák, 2001;Tóth et al, 2003Tóth et al, , 2011 and 3-deoxy-1,2:5,6-di-O-isopropylidene-3-methylene-α-d-ribo-hexofuranose II (Acton et al, 1979) were reacted with functionalized thiols (IIIa-IIIh). The reactions were carried out at ambient temperature with a 2 : 1 thiol : alkene molar ratio and irradiation at λ max = 365 nm for 15 min in the presence of the cleavable photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DPAP).…”
Section: Resultsmentioning
confidence: 99%
“…To produce carbon-sulfur-linked glycoconjugates by the proposed thio-click approach, 3,4,5,7-tetra-Obenzoyl-2,6-anhydro-1-deoxy-d-gluco-hept-1-enitol I (Tóth & Somsák, 2001;Tóth et al, 2003Tóth et al, , 2011 and 3-deoxy-1,2:5,6-di-O-isopropylidene-3-methylene-α-d-ribo-hexofuranose II (Acton et al, 1979) were reacted with functionalized thiols (IIIa-IIIh). The reactions were carried out at ambient temperature with a 2 : 1 thiol : alkene molar ratio and irradiation at λ max = 365 nm for 15 min in the presence of the cleavable photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DPAP).…”
Section: Resultsmentioning
confidence: 99%
“…(dd, 1H, J 4 ,5b = 6.1 Hz, H-5b ), 2.13, 2.10, 2.09 (3s, 9H, 3OAc). 13 -6-mercapto-9-(2 ,3 ,4 ,6 -tetra-O-acetyl-β-D-mannopyranosyl) …”
Section: General Methods For the Preparation Of 6-mercapto-9-(per-oacementioning
confidence: 99%
“…Among them, the 2 -deoxyribonucleosides proved to be effective against ascites Sarcoma 180 and Nakahara-Fukuoka sarcoma in mice and they also inhibited the growth of WI-L2 human lymphoblastoid cells. [12,13] In recent years, pyranosyl nucleosides are viewed as important modifications of natural nucleosides, offering promising avenues in the development of novel bioactive agents with promising therapeutic potential. [14][15][16][17][18][19][20][21][22][23][24] In our previous investigations, we demonstrated that base-modified pyranonucleosides rank among the most potent glycogen phosphorylase (GP) [25,26] and thymidylate synthase (TS) [27] inhibitors, and were endowed with a pronounced cytostatic and antiviral action.…”
Section: Introductionmentioning
confidence: 99%
“…The foregoing led Acton et al40 to synthesize the a -and P-anomers of 3'-hydroxymethyl-TGddR. Both of these were effectively phosphorylated in a Mecca lymphosarcoma in mice, and incorporated as terminators of short chains of DNA.…”
mentioning
confidence: 98%